KARAKTERISTIK BIOPLASTIK PATI SAGU (METROXYLON SP.) SETELAH PAPARAN CAHAYA ULTRAVIOLET - Sulaeman, Budiawan; Arman, Lukmanul Hakim (Jurnal Rekayasa Mesin, 2025)
This study aims to explore the characteristics of sago starch (Metroxylon sp.) after exposure to ultraviolet (UV) light, using a local sago variety known as Tawaro. Sago starch underwent Heat Moisture Treatment (HMT) to achieve 0% water content. Furthermore, this sago starch was used as a raw material for bioplastic production. The results of preliminary tests showed a tensile strength of 0.227 N/mm² (D0). Biodegradability testing was carried out on bioplastics exposed to UV light for 24 hours (D1UV24), 48 hours (D2UV48), and 72 hours (D3UV72). Fourier Transform Infra-Red (FTIR) analysis was used to identify the absorption patterns resulting from UV exposure. The results showed consistent absorption patterns before and after UV treatment, with no changes in functional groups or the emergence of new functional groups. However, changes detected in the intensity of the OH band broadening indicate photodegradation or oxidation. This is due to the formation of hydrogen bonds between the –OH groups of starch and glycerol. In addition, photodegradation affects mechanical properties, especially tensile strength. D1UV24 (0.406 N/mm²) and D2UV48 (0.619 N/mm²) showed an increase in tensile strength, while D3UV72 (0.538 N/mm²) decreased. This decrease was caused by prolonged oxidation, activating the polymer chain with free radicals. Contact angle testing showed that after the photodegradation process, the bioplastic became hydrophilic. These characterization data provide insight that Tawaro sago starch with 0% water content has the potential to be applied and developed as an environmentally friendly packaging product.